POTENSI WISATA EDUKASI BUDAYA DI MUSEUM LAYANG-LAYANG INDONESIA JAKARTA - Chanirunnisa; Lenny Yusrini (LPPM and Travel Operation Department Universitas Asa Indonesia, 2017)
This research’s aim is to know the potency of the cultural education tour of the Museum LayangLayang Indonesia Jakarta Selatan. The method used to obtain the potency is the SWOT analysis by identifying the potential components of Museum Layang-Layang Indonesia using the 5As theory. .The result of this research shows that the internal and external factors are all in the first quadrant, or in other words, the potency can be developed using agrressive strategy.